Development of Environmental Decision Support System for Sustainable Smart Cities in India - Shruti S.; Singh P.K.; Ohri A.; Singh R.S. (My University, 2025)
In the era of advanced technologies, information and communication technology (ICT) is the crucial component for developing Smart Cities. The topical studies indicate that ICT is primarily ignored to improve environmental sustainability in Smart Cities. The present research is an initial effort to develop a web-based Environmental Decision Support System (EDSS) for Sustainable Smart Cities in India (SSCI). The application developed evaluates a city's performance on a set of 24 environmental indicators, which is broadly categorized into four domains: Solid Waste Management (SWM), Water Supply Management (WSM), Sewerage, Sanitation, and Stormwater Management (SSS), and Ambient Environment Condition (AEC). EDSS-SSCI can serve as a valuable tool for policymakers in benchmarking a city's existing environmental scenario and grade it on a scale range of critically low, poor, fair, good, and excellent. The developed tool gives information about the city's performance in each domain along with three priority indicators which are decided on the basis of critical performance and higher weights given through the Delphi technique. This study presents the application to a real case study in Varanasi city, which identifies that its environmental sustainability smartness score exists in poor range and the focused attention for improvement is AEC domain. The study outcomes of the application developed will be beneficial for policymakers to define and drive the planning action towards developing Environmentally Sustainable Smart Cities in India. © 2022 American Institute of Chemical Engineers.